2015
DOI: 10.1016/j.joca.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of the effectiveness of a non-pharmacological multidisciplinary face-to-face treatment program on daily function compared to a telephone-based treatment program in patients with generalized osteoarthritis

Abstract: We found no differences in treatment effect between patients with GOA who followed a non-pharmacological multidisciplinary face-to-face self-management program and those who received a telephone-delivered program. Besides, our findings demonstrated limited benefits of a self-management program for individuals with GOA. Dutch Trial Register trial number: NTR2137.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 39 publications
1
36
0
5
Order By: Relevance
“…In total, 158 patients were included. For more details on the study population, we refer to the clinical study .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 158 patients were included. For more details on the study population, we refer to the clinical study .…”
Section: Methodsmentioning
confidence: 99%
“…As such, research on (the management of) GOA is very limited. Recently we evaluated the effectiveness of a nonpharmacologic, multidisciplinary, face‐to‐face treatment program versus a telephone‐based treatment program on daily function for individuals with GOA . That study showed small, nonsignificant differences in effectiveness on daily function and other clinical outcomes between both treatment programs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research 43 , an a priori sample size of 322 participants (161 per group) would provide 80% power at 5% level of significance (two-sided unpaired t-test) to detect a mean difference of 0.35 (standard deviation 1.00) in the number of consultations in secondary health care between groups, anticipating a maximum loss to follow-up of 20%, assuming a normal distribution.…”
Section: Sample Sizementioning
confidence: 99%
“…This study has an observational cross-sectional design; research questions were answered by secondary analyses of data from four studies performed in the Netherlands in four different populations: (1) patients with knee or hip OA in primary care [26], (2) patients with generalized OA in secondary care [27], (3) patients with knee or hip OA who underwent TJA [23,28], and (4) the general population [29]. Only data of subjects ≥ 50 years were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Maartenskliniek at Nijmegen in 2010 were included if they were clinically diagnosed with generalized OA and referred by their rheumatologist for multidisciplinary treatment. A total of 147 patients completed baseline assessments [27].…”
Section: Patients Who Visited the Outpatient Department Of The Sintmentioning
confidence: 99%